(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Rapid urbanization, along with uncontrolled urban expansion and outdated management processes, may result in a loss of space that is underutilised or ignored in metropolitan areas. These areas are referred to as lost space in this study. It may be located at anyplace that is not connected to a lively location. These areas may be changed into a viable public place with economic, social, and ecological significance. The loss of urban space owing to uncontrolled growth is a regular occurrence in most cities. However, careful urban regeneration might be a process that creates new chances by repurposing lost area such that it becomes useful and improve people’s health, happiness, and well-being by using a community’s assets, inspiration, and potential to achieve future objectives such as city social and economic growth. The purpose of this article is to address the use of lost space in urban areas. It will also provide some strategic advice on how to utilise the ‘lost spaces’.